Sheep wool-derived hydrolyzed keratin from tannery waste of the tanning industry using perhydrol - Prayitno, Prayitno; Rahmawati, Dona; Griyanitasari, Gresy (Majalah Kulit, Karet, dan Plastik, 2017)
Sheep wool waste discharged from leather tanning industry recently has posed a problem in relation to its treatment because of its sizeable quantity and its difficulty to degrade. Wool is composed mainly of keratin. It is a protein with a high content of disulfide bonds which cause the protein keratin cannot dissolve in water and resist of diluted acids and alkalis. Keratin can be hydrolyzed to produce keratin hydrolysates which have many benefits such as for cosmetic additives. Research into the use of waste wool of sheep originated from the sheep leather tanning industry had been performed by using a hydrolyzed system to produce protein keratin. The waste wool used came from unhairing by painting and conventional unhairing. Hydrolysis was done using hydrogen peroxide 50% amounting to 70 ml for every 40 gr of wool. Hydrogen peroxide was added to wool immersed in the 0.5 M NaOH solution for three hours. The length of hydrolysis ranged from 4, 5, to 6 hours and the mix was stirred shortly every 1 hour followed by filtration using a coarse sieve. To precipitate the hydrolyzed keratin, the pH was decreased to 4-5 using the 2 M HCl solution and after separation of the precipitation, it was dried in the oven at a temperature not more than 50 oC for 2 days. The research findings showed that a maximum of 69.19% of keratin hydrolysates was generated using the raw material of waste wool through a conventional process with a total of hydrolysis time by 6 hours, whereas the maximum protein generated was 66.99% using waste wool through a conventional process with a total of hydrolysis time by 4 hours. The FTIR test showed the presence of groups of amides, cysteic acids, and cystine-S-monoxide.